Physiological differences during exercise in water and on cycle ergometer for synchronised swimmers - Lobenius, K. (Biomechanics and Medicine in Swimming IX, 2003)
INTRODUCTION Synchronized swimming is a complex sport with a demand for several different capacities. The most important one for performance is unknown though. Knowledge about these capacities and how to test them, enhances the ability to understand the demands of the sport and to draw guidelines for training. The aims of this study were to; 1) establish physiological and physical characteristics, 2) compare maximal aerobic capacity on cycleergometer and during exercise in water (eggbeater), 3) evaluate the effect of two training models, and 4) investigate possible new test methods for exercise in water. METHODS The VO2max (named VO2peak due to problems to reach VO2max for some subjects) for eight synchronized swimmers was measured both during a cycleergometer test (CY) and in water by an eggbeater test (MEG). A submaximal eggbeater test (SEG) and a routinetest producing judges scores, was also performed in the water. The tests took place before and after a 12week-training period consisting of 3x20 min/week replaced technical training with submaximal cycling (n=4) and swimming (n=4), according to an interval method. RESULTS VO2peak was higher during the MEG compared with the CY; 10.6 % when expressed in absolute values (3.24 vs 2.93 l/min, p<0.001) and 10.4 % when related to body weight (53.1 vs 48.1 ml/kgxmin, p<0.001). A correlation between VO2peak at the two tests was found. For l/min 0.87 and for ml/kgxmin 0.91 (p<0.001). To further study the agreement between the tests a Blend-Altmanplot was made. This shows that the range of differences between VO2peak for the two tests is quite large. Both models of training (cycle and swim training) resulted in similar effects. At a specific load at the SEG, the work economy improved 10.0 %, (a 10.0 % lower VO2 consumption), and the [La] was 41.6 % lower, (p<0.05). The judges scores were also higher (p<0.05). A difference in VO2peak neither for l/min nor ml/kgxmin could be shown. DISCUSSION The higher VO2peak during the MEG could reflect a greater muscle mass involved and hence a greater oxygen demand (the arms were used for sculling). MEG could also be a specific test for SS which enables them technically, physiologically and psychologically to reach higher values during the MEG. The large range of differences between the two tests shows, despite the correlation between them, that the agreement between them is quite bad and that the tests should not be used interchageably. The relationship between them and the usefulness of the MEG, for example to predict a performance needs to be further investigated. The improvement of the work economy, La elimination and judges scores shows that the submaximal training together with ordinary training was sufficient to improve these variables but not VO2peak and that the submaximal variables could be more important for routineperformance.